The Effect of the Implementation of Mind Mapping Method on Critical Thinking Skills in Civic Education Learning - Sari, Resti Anika; Murdiono, Mukhamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
One of the efforts made to produce quality human resources in a developing country like Indonesia is to carry out development in all fields. In the field of education, various efforts to improve the quality of education are always carried out. This study aims to analyze the effect of the implementation of Mind Mapping method on the critical thinking skills of grade X students in civic education learning. This research is a quasi-experimental study using quantitative approach. The research sample was 62 students divided into 2 classes who were selected using random sampling technique. Data were collected by conducting pre-test and post-test. Hypothesis testing using t-test analysis with a significance level of the analysis results was determined at 5%. The result showed that there was an effect of the implementation of Mind Mapping method in learning civic education on the critical thinking skills of class X students. This is indicated by the increase of Â of the post-test that is 7.923. In addition, the ttable on df 60 was 2.000, and the significance value of 0.000 was smaller than the significance level of 5% (0.000 < 0.05). Mind mapping as a learning method can be used as a solution to improve students' critical thinking in the learning process in order to achieve learning goals.